Recombineering in Streptococcus mutans Using Direct Repeat-Mediated Cloning-Independent Markerless Mutagenesis (DR-CIMM) - Shan Zhang; Shan Zhang; Zhengzhong Zou; Jens Kreth; Justin Merritt; Justin Merritt (Frontiers in Cellular and Infection Microbiology, 2017)
Studies of the dental caries pathogen Streptococcus mutans have benefitted tremendously from its sophisticated genetic system. As part of our own efforts to further improve upon the S. mutans genetic toolbox, we previously reported the development of the first cloning-independent markerless mutagenesis (CIMM) system for S. mutans and illustrated how this approach could be adapted for use in many other organisms. The CIMM approach only requires overlap extension PCR (OE-PCR) protocols to assemble counterselectable allelic replacement mutagenesis constructs, and thus greatly increased the speed and efficiency with which markerless mutations could be introduced into S. mutans. Despite its utility, the system is still subject to a couple limitations. Firstly, CIMM requires negative selection with the conditionally toxic phenylalanine analog p-chlorophenylalanine (4-CP), which is efficient, but never perfect. Typically, 4-CP negative selection results in a small percentage of naturally resistant background colonies. Secondly, CIMM requires two transformation steps to create markerless mutants. This can be inherently problematic if the transformability of the strain is negatively impacted after the first transformation step, which is used to insert the counterselection cassette at the mutation site on the chromosome. In the current study, we develop a next-generation counterselection cassette that eliminates 4-CP background resistance and combine this with a new direct repeat-mediated cloning-independent markerless mutagenesis (DR-CIMM) system to specifically address the limitations of the prior approach. DR-CIMM is even faster and more efficient than CIMM for the creation of all types of deletions, insertions, and point mutations and is similarly adaptable for use in a wide range of genetically tractable bacteria.